Different forms of civilizations and the development of woodlands: systems of interactions - Küster, Hansjörg (Studia Historiae Oeconomicae, 2024)
The development of woodland was influenced by different management since some thousands of years. During prehistoric times settlements were founded and given up after some decades. In connection with this, a secondary succession of woodland took place. The spread of beech in Central Europe was favoured and some other tree species expanded in other parts of Europe. This is documented by pollen diagrams. During historic times woodland exploitation was intensified. Some tree species became rarer by more intensive management such as beech. So human impact did not have generally the same effect on the development of woodlands. As management influenced the development of woodland more than climatic changes it is likely that this will also happen in the future. Pollen diagrams are not historic sources but can be well paralleled with historic sources. It is an advantage of pollen diagrams that they encompass a total development of vegetation and do not only reflect a single event at special points of time.